EVALUATION OF THE LEVEL OF PROTECTION CONFERRED BY A VACCINATION SCHEME AGAINST THE INFECTIOUS BURSAL DISEASE IN BROILERS USING THE DEVENTER FORMULA - Paredes V., Walter (2009)
The present study evaluated the conferred protection by a program of vaccination at an age that was determined by the Deventer formula against a challenge with a standard strain of the Infectious Bursal Disease virus (IBDV) in broiler chickens. There were three experimental groups. The group A was vaccinated at 10 days of age with a Lukert strain (intermediate-mild) and at 18 days with CE strain (intermediate-intermediate); group B vaccinated at 21 days old (according to the Deventer formula) with the 228TC strain (intermediate-intermediate); and group C were not vaccinated (control). At 35 days of age, 45 birds of each group were challenged with a standard strain F 52/70 of the IBDV. The protection was measured through clinical signs, bursal index (B.I.), gross and microscopic lesions, and serology. All groups presented clinical signs and bursal oedema until 10 days post challenge. The values of B.I. in the three groups were compatible with bursal atrophy and the histopathology lesions were severe in the vaccinated groups. Seroconversion was not observed until the end of the study. The obtained results indicated that birds in none of the experimental groups were protected against the clinical disease until 10 days post challenge. The best protection was observed in the group A in comparison group B but without statistical difference.